Implementation of The CIPP Evaluation Model in Students’ Writing Skills for Grade X SMK Negeri 1 Purworejo - Sholeh, Khabib; Hermayani, Shalma; Purwanto, Joko; Kadaryati, Kadaryati (ppjbsip, 2025)
So far, the evaluation of writing instruction has not fully considered comprehensive assessment aspects, causing students to struggle in effectively expressing their ideas in writing. Meanwhile, writing skills have become a crucial necessity in today’s era of technological advancement. This study aims to describe the implementation process and evaluation results of the CIPP model in learning writing skills in grade X at SMK Negeri 1 Purworejo for the 2024/2025 academic year. The research was conducted using a qualitative case study approach. Data collection techniques included literature review, observation, and note-taking. The literature review involved analyzing lesson plans designed by teachers, observation was conducted during learning activities and note-taking was used to document findings from the observations. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data presentation, and data verification. The results were presented narratively, accompanied by tables and diagrams. The findings indicate a gap between planning and implementation in the evaluation process, yet the average writing skill scores demonstrate success. These findings highlight the importance of evaluation in learning to enhance effective writing skill development. Abstrak Selama ini, evaluasi pembelajaran menulis belum memperhatikan aspek evaluasi secara menyeluruh sehingga peserta didik masih mengalami kesulitan dalam menuangkan ide-ide mereka secara efektif dalam menulis. Sementara itu, kemampuan menulis menjadi kebutuhan utama di era perkembangan teknologi sekarang. Penelitian ini bertujuan untuk mendeskripsikan proses pelaksanaan serta hasil evaluasi model CIPP dalam pembelajaran keterampilan menulis di kelas X SMK Negeri 1 Purworejo tahun pelajaran 2024/2025 yang dilaksanakan dengan metode penelitian kualitatif pendekatan studi kasus. Pengumpulan data diambil dari teknik pustaka, teknik simak, dan teknik catat. Teknik pustaka berupa administrasi pembelajaran yang dirancang oleh guru, teknik simak digunakan saat menyimak kegiatan pembelajaran, dan teknik catat digunakan untuk mencatat dari hasil simak. Analisis data dilakukan dengan menggunakan model analisis interaktif Milles dan Huberman yang terdiri dari reduksi data, penyajian data, dan verifikasi data. Penyajian hasil analisis dibuat dalam bentuk naratif disertai tabel dan diagram. Hasilnya menunjukkan kesenjangan antara perencanaan dan pelaksanaan dalam proses pelaksanaan evaluasi, tetapi rata-rata nilai hasil keterampilan menulis menunjukkan keberhasilan. Temuan-temuan ini menyoroti pentingnya evaluasi dalam pembelajaran untuk meningkatkan pembelajaran keterampilan menulis yang baik.